“Histórias em múltiplos fios”: o ensino de manualidades entre mulheres negras em Rio Grande (RS – Brasil) e Capitán Bermúdez (Sta. Fe – Argentina) (re)inventando pedagogias da não-formalidade ou das tramas complexas - Cunha, Aline Lemos da (Universidade do Vale do Rio do Sinos, 2010)
This thesis is a survey about the teaching and learning of Manual Works (Handicrafts) with black women in Rio Grande (RS – Brazil) and Capitán Bermúdez (Santa Fe – Argentina). Such survey was elaborated from the following theme: “Non-formalities Pedagogy or Complex plots (re)invented by black women through teaching and learning of manual works (handicrafts) and the seek for emancipation”. There were held meetings in Brazil – city of Rio Grande – with women belonging to the Afro ethnic group that have experience in professions historically destined to women and particularly to black women, being: domestic labour (housekeepers, washers, cooks …), babysitting and hair embellishment linked to hair plaits (corn rolls). Also took part in this investigation, in Argentina – city of Capitán Bermudez, women that, even not expressing the ethnic group which they are part of, demonstrate phenotypically pointers of being descendents from Argentinean Indians, acting in the same professions. At a first sight it may seem wron
Keywords: mulheres negras; pedagogias da não-formalidade; trabalhos manuais; educação; black women; handicrafts; non-formality pedagogy; education; Ciências Humanas